Coordination of Over Current Relay Using Optimization Technique - Sonia Kolhe; Prajakta Kasulkar (Journal of Power Electronics and Devices, 2021)
In this paper we proposed a solution for overcurrent relay utilizing Crow Search Algorithm (CSA). CSA is a meta-heuristic optimizer algorithm, this method is derived from crow expeditious shrewdness probing technique. This algorithm can be easily operated by transmuting two parameters like flock size and iterations. With the avail of CSA we can now handle any kind of fault, connection error, distribution error can be overcome and smooth power transfer. The OCRs decide which component of the puissance system has to come into action during a fault in order that the faulty section is isolated and does not interrupt the potency system, with certain constraints like adequate coordination tolerance and without extra disruptions.